OBSERVATIONS ON THE RACQUETTIPS OF THE MOTMOTS TAIL - WAGNER, H (Instituto Politécnico Nacional, Escuela Nacional de Ciencias Biológicas, CD MEXICO, DF, MEX, 1950)
In motmotus tail shape is due to structural weakness of the barbs except those at the tip The barbs are not "purposefully" removed as has often been reported Intensity of the tail wagging is correlated with breeding activity, and is initiated by any dis
Z ANAL CHEM FRESENIUS
Keywords: OBSERVATIONS, RACQUET TIPS, MOTMOTS TAIL; CIENCIAS AGRARIAS; BIOLOGIA ANIMAL; ZOOLOGIA GENERAL